2022
DOI: 10.1159/000527726
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Incidence of Guillain-Barré Syndrome during the COVID-19 Pandemic: A Retrospective Population-Based Study

Abstract: Background: Guillain-Barré syndrome is an immune-mediated acute inflammatory polyneuropathy that is associated with various triggers, including certain infections and vaccines. It has been suggested that both SARS-CoV2 infection and vaccination may be triggering factors for Guillain-Barré syndrome, but evidence remain equivocal. Here we conducted a population-based incidence study of Guillain-Barré syndrome spanning the three years immediately prior to and the two years during the pandemic. Methods: Cases wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…On the other hand, during the first five pandemic months, the incidence of GBS in the UK, as derived from the National Immunoglobulin Database, was reduced compared with the same period of the previous 5 years [9]. Similar results were recently reported in South Korean and in Swedish studies [10, 11]. These contrasting findings make the debate on GBS and SARS‐CoV‐2 infection heated.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…On the other hand, during the first five pandemic months, the incidence of GBS in the UK, as derived from the National Immunoglobulin Database, was reduced compared with the same period of the previous 5 years [9]. Similar results were recently reported in South Korean and in Swedish studies [10, 11]. These contrasting findings make the debate on GBS and SARS‐CoV‐2 infection heated.…”
Section: Introductionmentioning
confidence: 66%
“…The risk of developing GBS in northern Italy during the first COVID‐19 pandemic wave was 2.85 times increased compared with the same period of the previous year, whereas, when considering the first pandemic year, the overall GBS risk was in some countries 0.17 times reduced [7, 8, 10, 11]. In northern Italy the GBS risk decreased from 2.6 in March–April 2020 to 1.41 considering the whole first pandemic year [7, 28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, the opposite results were obtained in the UK, where, according to data from the national immunoglobulin database, there was a decrease in the number of cases [69]. A similar situation was also observed in Sweden [70], Korea [71,72], and Portugal [73]. The reduction in the number of GBS cases may be due to the protective measures introduced during the pandemic.…”
Section: Covid-19 and Guillain-barre Associationmentioning
confidence: 90%
“…38 The incidence of GBS can increase during outbreaks of infectious diseases, with the most recent being the Zika virus epidemics in 2013 (French Polynesia) and 2015-2016 (Latin America). 35 While COVID-19 has also been linked with an increase of GBS in some studies, 39,40 data remain conflicting. A large population-based study from Israel found with COVID-19 an increased risk of GBS, while the Pfizer vaccine was associated with a decreased risk of GBS.…”
Section: Epidemiologymentioning
confidence: 99%